2019
DOI: 10.1108/jtf-11-2018-0067
|View full text |Cite
|
Sign up to set email alerts
|

Importance-performance analysis to inform visitor management at marine wildlife tourism destinations

Abstract: Purpose The purpose of this paper is to postulate that the technique of Importance-Performance Analysis (IPA) is currently underutilised in visitor management studies reported in the peer-reviewed marine wildlife tourism (MWT) research literature. Further, this paper provides insight into how IPA could inform future research and management of tourism experiences at marine wildlife destinations. Design/methodology/approach This paper synthesises learning gained from the natural area tourism and recreation lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 68 publications
0
16
0
1
Order By: Relevance
“…The synthesis presented in this article is informed and inspired by the extensive systemic literature reviews and the UGI research that is reported in several earlier articles by the authors [2,[14][15][16][17][18]22,26]. In addition, 32 globally focused review articles and 20 geographically specific UGI research articles are directly cited to support the synthesis presented in this article (Tables 1 and 2 below).…”
Section: Methods and Applicationmentioning
confidence: 89%
See 4 more Smart Citations
“…The synthesis presented in this article is informed and inspired by the extensive systemic literature reviews and the UGI research that is reported in several earlier articles by the authors [2,[14][15][16][17][18]22,26]. In addition, 32 globally focused review articles and 20 geographically specific UGI research articles are directly cited to support the synthesis presented in this article (Tables 1 and 2 below).…”
Section: Methods and Applicationmentioning
confidence: 89%
“…The HNCT provides multiple practical opportunities for modern cities to respond to climate change by cultivating and increasing pro-environmental behaviors, advocating for the creation and implementation more UGI assets, improving practices and approaches to current community planning and urban development regimes, and advocating for the renaturing of urban communities [20][21][22][23]. The level of human-nature connection is seen to be a reliable predictor for pro-environmental behavior [20].…”
Section: Human-nature Connection Theorymentioning
confidence: 99%
See 3 more Smart Citations